Ameliorating Effect of Red Fruit (Pandanus conoides Lamk) Oil in Streptozotosin-Induced Diabetic Peripheral Neuropathy Rat Model: role of oxidative and neuroinflammatory pathways - Indah Tri Lestari; Kusnandar Anggadiredja; Afrillia Nuryanti Garmana; Ratna Annisa Utami (Journal of Pharmacopuncture)
Objectives: Diabetic peripheral neuropathy (DPN) is the most common cause of neuropathy worldwide, with oxidative and inflammatory being the pathways involved in the disease pathology. Red fruit (Pandanus conoides Lamk) oil (RFO) is known to have potent antioxidants and anti-inflammatory activities. To investigate the effects of RFO in a rat model of streptozotocin-induced DPN. Methods: Male Wistar rats were induced with 55 mg/kg streptozotocin (STZ) intraperitoneally. Rats with fasting blood glucose ≥ 200 mg/dL were assigned into groups treated with vehicle, pregabalin 30 mg/kg, and 0.3, 0.6, or 1.2 mL/kg RFO, respectively. The treatments were given for 3 weeks, six weeks after STZ induction. Neuropathic pain was evaluated by cold allodynia and thermal hyperalgesia tests. Histopathological changes of the pancreas and sciatic nerve were evaluated by the Gaussian adaptive threshold method. Feed and drinking intake, blood glucose levels, body weight, and sciatic nerve proinflammatory cytokines were also measured. Results: There were increases in blood glucose levels, feed and drink intake, levels of MDA, TNF-α;, IL-6, NFκB, and iNOS; decrease in catalase level; and damage to the sciatic nerve in the vehicle-treated DPN rat model compared with normal rats (p < 0.05). Meanwhile, significant decrease in weight, number of pancreatic β cells, latency times for thermal hyperalgesia as well as cold allodynia were observed in this group of rats. RFO administration at 0.6 and 1.2 mL/kg significantly improved all of the measured indices, except for iNOS, where only decreasing trend was observed. Pregabalin did not affect blood glucose levels, body weight or pancreatic β cells but improved thermal hyperalgesia as well as cold allodynia, the sciatic nerve cell counts, TNF-α; IL-6, NFκB, and iNOS levels. Conclusion: RFO improves DPN by neuroprotective effect through the involvement of the oxidative and neuroinflammatory pathways.